The impact of novel material processing methods on component quality, life and performance - KAYNAK, YUSUF (Elsevier B.V., 2014)
Surface and subsurface characteristics of structural components for use in production equipment and machines, depending on the functions and their usage in service, can be the critical aspect from the service life viewpoint. Generated surface and subsurface characteristics of manufactured components affect functional performance with progressively deteriorating wear, corrosion and fatigue resistance, and consequently determine the effective life of components of such machines and equipment in various industries including aerospace, automotive and power industries. Developing advanced processing methods and predictive models to control surface integrity characteristics of components for achieving improved product life and performance has been an area of significance in advanced manufacturing. This paper summarizes and highlights recent advances in developing novel manufacturing techniques involving cryogenically-assisted processing (machining, burnishing and friction-stir processing) on a range of aerospace, automotive and biomedical metal alloys (Co-Cr-Mo, AZ3IBMg, NiTi, Inconel 718, SS 303 stainless steel, and Al 7050) for achieving enhanced product quality, life and performance at component level. This study presents an analysis of surface integrity involving severe plastic deformation (SPD) of these materials induced by cryogenically-assisted manufacturing processes, by showing the resulting product/component performance enhancement through the generation of controllable ultra-flne/nano grain structures in the surface layers of the products/components. This grain refinement is also often accompanied by improved wear and corrosion resistance properties and the generation of compressive residual stresses enabling improved fatigue life, along with more favorable phase transformation in these cryogenically-processed materials. Experimental results are compared with predictions obtained from numerical models and simulations. Encouraging trends are observed with potential for applications in industry. © 2014 Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
Keywords: Cryogenic cooling; Product performance; Service degradation; Service life; Severe plastic deformation; Surface integrity